Empowering Academic Excellence: Pre-National Science Olympiad Training for Elementary and Junior High School Students - Istikomah; Sheilla Rully Anggita; Hartono; Fadhillah; Siti Nurfadhillah Murtado (Community Research and Application Journal (CRAJ), 2025)
This community service activity aimed to enhance students' academic competency and preparedness for the National Science Olympiad (OSN) 2023 in Mathematics and Natural Sciences at elementary and junior high school levels. The program, organized by the Physics Department of Universitas Islam Negeri Walisongo Semarang in collaboration with the Association of Madrasah Science Enthusiasts (Perkumpulan Pegiat Sains Madrasah), was conducted online via Zoom Meeting. The training covered eight comprehensive sessions including Kinematics and Mechanics, Forces, Rotational Dynamics, Oscillations and Waves, Electricity and Magnetism, Solar System, Optics, and Temperature and Heat, along with two simulation sessions. Despite challenges such as network connectivity issues and varying participant readiness levels, the program successfully provided intensive coaching to OSN participants and their supervising teachers from elementary (SD/MI) and junior high school (SMP/MTs) levels. This initiative demonstrates the importance of systematic academic preparation and highlights the role of higher education institutions in supporting K-12 education excellence through collaborative mentoring programs.